Karykatura jako narzędzie polityki państwa - Kakarenko, Ksenia (Czasopismo Prawno-Historyczne, 2018)
Satire in all countries is protected as a manifestation of public mood and for this reason it is not subject to criminal liability. Caricature is a specific kind of satirical art. During an analysis of the history of the USSR and Poland, one can highlight the special role of caricature in the implementation of a state’s international policy. It served as an instrument of reaching the least educated social strata with state propaganda. It is also worth noting that caricature played a smaller or a larger part for the state at different periods of history.